2005
DOI: 10.1002/cncr.21273
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between annual volume of cystectomy, professional staffing, and outcomes

Abstract: The polymer nanocomposite samples have been prepared by solution embedding of CdS nanoparticles in polyurethane (PU). The structural properties have been studied by scanning electron microscopy (SEM) and atomic force microscopy (AFM). SEM and AFM images represent the dispersion of CdS nanoparticles in a polymer matrix. The permittivity of nanocomposite samples increases with temperature due to formation of new dipoles or accumulation of charge carriers in a nanoparticle‐‐polymer interface. The increase in perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
1
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 51 publications
6
91
1
8
Order By: Relevance
“…Hospitals that perform a high volume of radical cystectomies have lower mortality and complication rates than lowvolume centers. 162 Some have suggested that hospitals offering radical cystectomy should perform more than 10 cases annually. 162 Others have evaluated surgeon volume and, because of improved patient outcomes with higher volumes, have recommended that 10 radical cystectomies should be performed per surgeon annually to maintain proficiency.…”
Section: Radical Cystectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitals that perform a high volume of radical cystectomies have lower mortality and complication rates than lowvolume centers. 162 Some have suggested that hospitals offering radical cystectomy should perform more than 10 cases annually. 162 Others have evaluated surgeon volume and, because of improved patient outcomes with higher volumes, have recommended that 10 radical cystectomies should be performed per surgeon annually to maintain proficiency.…”
Section: Radical Cystectomymentioning
confidence: 99%
“…162 Some have suggested that hospitals offering radical cystectomy should perform more than 10 cases annually. 162 Others have evaluated surgeon volume and, because of improved patient outcomes with higher volumes, have recommended that 10 radical cystectomies should be performed per surgeon annually to maintain proficiency. 163 Increased surgeon volume may improve outcomes because of better clinical judgement, improved technical proficiency in the operating room, and a better global understanding of the disease.…”
Section: Radical Cystectomymentioning
confidence: 99%
“…Indeed, previous studies have documented the effect of AHC on RC outcomes. 3,4 Specifically, RC performed at high AHC hospitals were less frequently associated with blood transfusions, less frequently resulted in length of stay beyond the median and were associated with fewer in-hospital mortality rates. That being said, academic status persistently predicted lower complication rates even after adjusting for AHC.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Surgeon and hospital annual caseloads represent established predictors of a variety of RC outcomes, according to the "practice makes perfect" hypothesis. 3,4 Other predictors of favourable outcomes consist of younger patient age, favourable baseline comorbidity profile and select geographical region. [3][4][5][6] However, to the best of our knowledge, the relationship between institutional academic status and postoperative outcomes following RC has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation